Pengaruh Penggunaan Tepung Daging Bekicot (Achatina fulica) pada Pakan Buatan terhadap Pertumbuhan, Rasio, Konversi Pakan dan Tingkat Kelulushidupan Benih Ikan Patin (Pangasius pangasius) [Effect of Use of Snail Meat (Achatina fulica) for Artificial Diet on Growth, Food Convertion and Survival Rate Catfish (Pangasius pangasius)] - Boedi Setya Rahardja; Devieta Sari; Moch. Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
AbstractCurrently catfish is experiencing a fairly rapid growth, this is because the catfish is one of the important commodities in the fishery. Efforts to increase catfish production is to improve the quality of feed. The aim of this study is to observe effect of snail meat meal for growth rate, food conversion ratio and survival rate of catfish seeds. This research method is experimental with a Completely Randomized Design (CRD) with five treatments and four replications. The treatments were used: (A) 0% snail meat meal, (B) 10% snail meat meal and 30% fish meal, (C) 20% snail meat meal and 20% fish meal, (D) 30% snail meat meal and 10% fish meal and (E) 40% snail meat meal. The main parameters measured were growth, feed conversion ratio and survival rate. Supporting parameters measured were water quality. Analysis of the data used is Analysis of variance (ANOVA) and to know the difference among treatment using Duncan's Multiple Range Test. The results of this study showed that use of snail meat meal in feed formulation stastistically difference (p<0.05) for growth and survival rate of catfish seeds but not statistically difference (p>0.05) for feed conversion ratio. Water quality in maintenance media seed catfish is the temperature 0range between 26-31C, pH 7-8 and dissolved oxygen was 7.2-8.0 mg/L.